2020
DOI: 10.29271/jcpsp.2020.10.1063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Videothoracoscopy and Thoracotomy in Surgical Treatment of Pulmonary Hydatid Cyst Disease

Abstract: Objective: To evaluate the outcomes of videothoracoscopic and open surgeries for pulmonary hydatid cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…It showed that chest tube insertion duration was longer in the thoracotomy group than the VATS group [ 23 ]. The same results were reported in a 2020 study, which found that there was an early chest tube removal in the VATS group compared to the thoracotomy group [ 27 ].…”
Section: Discussionsupporting
confidence: 81%
“…It showed that chest tube insertion duration was longer in the thoracotomy group than the VATS group [ 23 ]. The same results were reported in a 2020 study, which found that there was an early chest tube removal in the VATS group compared to the thoracotomy group [ 27 ].…”
Section: Discussionsupporting
confidence: 81%
“…The use of a double-lumen endotracheal tube is important to prevent aspiration of the cyst contents into the tracheobronchial tree during the operation. 66 , 67 …”
Section: Surgerymentioning
confidence: 99%